Environmental change and development in Ladakh, Indian Trans-Himalaya - Humbert-Droz, Blaise; Dame, Juliane; Morup, Tashi (Springer Nature Switzerland, 2023)
Introduction -- Glaciers of Central Ladakh: Distribution, Changes and Relevance in the Indian Trans-Himalaya -- Floods and Debris Flows in Ladakh: Past History and Future Hazards -- Impact of 2010 Leh Cloudburst: a Psychological Perspective -- Traditional Mathematical Theories of Rainfall Prediction through Lotho as Practised in Ladakh -- The Contribution of Czech Researchers to the Botanical Survey of Ladakh -- The Adaptations of High-Altitude Mushrooms in the Cold Desert of Ladakh -- A Brief Description of Sacred Trees (lhachang) -- Environmental Change in Ladakh’s Changthang: a Local, Regional and Global Phenomenon -- Wildlife versus Livestock: Conservation Dilemma of the Pastoralists of Changthang -- Harnessing Traditional Knowledge for Wildlife Conservation in the Ladakh Trans-Himalaya -- Changing Production, Changing Consumption: Food System Transformation in Ladakh -- Eating Habits In and Around Leh Town -- Seeds of Change: A Review of Agricultural Developments in Central Zangskar -- Influences of Tourism, Indian Administration and Army on Community Identity Processes in Padum (Zangskar) -- “We Are Puppets in the Hands of Nature”: Road Construction and the Transformation of People-Environment Relationships in Ladakh -- Trade-Off between Continuity and Change in Leh District: an Emergy Evaluation in Time Series: 1999-2011.
Keywords: Klimaänderung; Ladakh